Pemakzulan Dalam Demokrasi Presidensial Indonesia: Antara Legalitas Konstitusional dan Legitimasi Politik - Sihombing, Desi Natalia (Department of Political Science, Faculty of Social and Political Science, Udayana University, 2025)
Impeachment in Indonesia’s presidential system, as regulated in the post-amendment 1945 Constitution, operates at the intersection of formal legal instruments and political practice. Using a qualitative method with juridical-normative and political-analytical approaches, this study examines the constitutional provisions alongside the political configuration of the DPR after the 2024 election. Findings show that while the legal framework prescribes a clear multistage process, its effectiveness is constrained by dominant ruling coalitions and elite interests, making impeachment politically improbable without a legitimacy crisis. Applying Weber’s theory of legitimacy, Thompson’s moral politics, Ackerman’s separation of powers in legitimacy crises, and Linz’s perils of presidentialism, this research argues that impeachment is both a legal and political arena. The study recommends procedural reforms to bridge formal legality and substantive legitimacy, emphasizing public accountability mechanisms to strengthen executive oversight and democratic resilience.